Théâtre immersif et jeu vidéo - Olivia Levet (Appareil)
Video games and human-computer interfaces, in their development, were fed by drama and performing arts in order to integrate the consideration of the user and the human in their design. Today, the appearance of an “immersive theater” confirms this rapprochement. Through the sociocritical analysis of the creative process of two plays, Greenhive Green by Punchdrunk Enrichment and The Lost Generation by Madame Lupin, this article draws a parallel between theater residency programs and playtests or early versions in the video game industry. Through a common vocabulary, processes and ambitions, immersive theater and video game seem to constitute a mirror to a dominant participatory ideology where the entrepreneurial, autonomous and self-reliant is valued, as suggested in the Adam Alston’s analysis of the Punchdrunk company’s work. However, like a participatory political theater – the Theatre of the oppressed developed by Augusto Boal –, some artists are appropriating these tools in order to construct art in a collaborative, critical way and in resistance to industry, where audience integration makes the co-construction of an aesthetic experience turned towards emancipation possible.